Upaya Meningkatkan Perilaku Masyarakat Menyediakan Jamban Sehat di Kabupaten Soppeng - Bakhrani A. Rauf; Muhammad Ardi; Faizal Amir (Seminar Nasional LP2M UNM, 2019)
The purpose of this research is to find out: (1) knowledge, attitudes, motivation, and behavior to provide healthy latrine before and after training, 2) the effect of training in increasing knowledge, attitudes, motivation, and behavior in providing people healthy latrine in Laringgi Village, Soppeng Regency. This research is an experimental research located in the village of Laringgi, Soppeng Regency. The amount of respondents are 25 households selected by the purposive sampling method. The variables considered are as follows: (a) behavior of providing healthy latrine, (b) knowledge about healthy latrine, (c) attitudes towards healthy latrine, and (d) motivation to provide healthy latrine before and after the experiment, (e) the effect of training on increased knowledge, attitudes, motivation, and behavior to provide healthy latrine. The experimental design used was one group pretest-posttest desigen. Analysis of the data used is descriptive statistical analysis and inferential statistical analysis. The analysis model used is the independent t-test. The results of the study are as follows: (1) knowledge, attitudes, motivation, and behavior of the people in the village of Laringgi, Soppeng Regency, providing healthy latrine before being trained in the low category, after being trained in the very high category, (2) Training has a significant influence on increased knowledge, attitudes, motivation, and people behavior towards healthy latrine in the village of Laringgi, Soppeng Regency.